Medical Transformation on the Legality of Inheritance Rights of Passive Eutanasia Applicants: Jasser Audah's Maqasidi Analysis - Dzulkifli Al-amin (Fakultas Syariah Institut Agama Islam Negeri Palu, 2024)
This research discusses ethical and legal dilemmas related to euthanasia in the perspective of Islamic law, especially regarding inheritance rights for passive euthanasia applicants. This research uses a normative juridical method with a conceptual approach to explore how Islamic law regulates inheritance rights in cases of passive euthanasia carried out on the basis of compassion. Euthanasia, both active and passive, remains a controversial issue. Legally in Indonesia, euthanasia is very close to Article 344 on murder as well as Article 304 of the Criminal Code and Article 173 of KHI on the causes of the loss of inheritance rights, but even so the implementation and interpretation are still debatable. From an Islamic perspective, murder can prevent inheritance rights, but there are differences of opinion among scholars regarding the type of murder in question. The results of this study show that the legal illat from the hadith and Islamic legal literature to conclude that the act of passive euthanasia, if done with good intentions and not aimed at accelerating the acquisition of inheritance, does not hinder inheritance rights.